Very severe aortic stenosis masquerading as acute coronary syndrome. Issue 12 (23rd December 2021) - Ghosh, Soumitra; Batta, Akash; Sharma, Yash Paul; Panda, Prashant
Abstract : Severe aortic stenosis (AS) may rarely present like acute coronary syndrome with increased cardiac biomarker despite having normal coronaries. Here we describe a case of very severe AS, who presented with exertional and rest angina and a high level of TnI. Angiography revealed normal coronaries. Echocardiography showed very severe AS with peak velocity of 5.08 m/s and maximum and mean gradient of 103 and 54 mm Hg, respectively. The patient subsequently underwent aortic valve replacement (AVR) successfully. Subendocardial ischaemia may occur in patients with severe AS during haemodynamic stress, even in the setting of normal unobstructed coronaries due to supply-demand mismatch. Subsequent degeneration and death of the cardiac myocytes cause cTnI elevation, which anticipates the start of the clinical downhill course in severe AS. Our case highlights the importance of thorough physical examination and early use of echocardiography in patients with angina to detect the presence of severe AS.